The effects of bilingualism and multilingualism on executive functions - Bernardo Kolling Limberger; Augusto Buchweitz (Fórum Linguístico)
Studies have shown that bilinguals and multilinguals have superior performance compared to monolinguals in nonlinguistic tasks that tap into executive functioning. However, studies of bilingual and multilingual advantages in linguistic tasks are fewer and the results are less consensual. In Brazil, the positive effects of executive functions in bilingualism have not been consistently identified in the bilingual populations, especially in speakers of the minority language Hunsrückisch (a German dialect). The main goal of this study was to investigate the performance of bilinguals and multilinguals speakers of Hunsrückisch compared to monolinguals in a nonlinguistic task, the Attentional Network Task, and in a linguistic task, the Sentence Comprehension Task. The results show that multilinguals were faster in comparison to monolinguals in the nonlinguistic task. The results for the linguistic task, in turn, show that the monolinguals had more facility to inhibiting the linguistic interference.